Abdominal massage: A review of clinical and experimental studies from 1990 to 2021 - Gaofeng Wang; Zepeng Zhang; Jiabao Sun; Xiangyan Li; Yunjie Chu; Daqing Zhao; Hongyu Ju; Xingquan Wu; Deyu Cong (Elsevier, 2022)
Objective: To systematically review the current state and holistic application of abdominal massage (AM). Design: A systematic review of qualitative evidence was conducted. All English articles exploring the topic of AM that had been published until the end of June 2021 were retrieved. Data sources: The PubMed, Cochrane library, and Embase databases were accessed. Some original texts were obtained from Google Scholar. Data extraction and synthesis: Two authors independently evaluated all search data to identify relevant studies. Disagreements were settled by discussion with a third author. Results were independently extracted into standardized sheets and checked for accuracy. Main results: A total of 107 full-text reports were eligible for inclusion. Adult digestive disorders, pediatric disorders, gynecological disorders, obstetric disorders, metabolic disorders, psychological disorders, the side effects of AM, and animal experiments accounted for 49.53%, 14.02%, 7.48%, 7.48%, 4.67%, 4.67%, 5.61%, and 6.54% of all these papers, respectively, with most reports focusing on clinical studies. Conclusion: The variety of diseases treated with AM is gradually increasing, and the treatment programs of AM for many diseases are being gradually optimized. Different forms of AM, especially mechanical AM, have been widely studied; the side effects of AM have also been considered; and the possible mechanisms of AM therapy continue to be discovered. In general, AM is an effective and safe therapy and can be widely used in various diseases, but further studies are necessary to clarify the mechanism of AM for different diseases. In the future, AM could become an even safer, more popular, and more modern therapy.